2022
DOI: 10.3390/rs14133168
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Freeze–Thaw Cycles in an Endorheic Basin on the Qinghai-Tibet Plateau Based on SBAS-InSAR Technology

Abstract: The freeze–thaw (F-T) cycle of the active layer (AL) causes the “frost heave and thaw settlement” deformation of the terrain surface. Accurately identifying its amplitude and time characteristics is important for climate, hydrology, and ecology research in permafrost regions. We used Sentinel-1 SAR data and small baseline subset-interferometric synthetic aperture radar (SBAS-InSAR) technology to obtain the characteristics of F-T cycles in the Zonag Lake-Yanhu Lake permafrost-affected endorheic basin on the Qin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…In recent decades, with climate warming, some changes have occurred in permafrost regions on the QTP, such as the active layer thickness [6,7], ground temperature of permafrost [6], permafrost extent [4], and thermokarst lakes [8]. These changes can cause surface settlement and serious hazards to the stability of the Qinghai-Tibet Railway and Qinghai-Tibet Highway [9,10]. Additionally, previous studies have shown that the amount of organic carbon stored in permafrost is approximately twice that of the atmospheric carbon content [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, with climate warming, some changes have occurred in permafrost regions on the QTP, such as the active layer thickness [6,7], ground temperature of permafrost [6], permafrost extent [4], and thermokarst lakes [8]. These changes can cause surface settlement and serious hazards to the stability of the Qinghai-Tibet Railway and Qinghai-Tibet Highway [9,10]. Additionally, previous studies have shown that the amount of organic carbon stored in permafrost is approximately twice that of the atmospheric carbon content [11].…”
Section: Introductionmentioning
confidence: 99%
“…Ground leveling measurements conducted at Wudaoliang leveling observation site are used to verify the InSAR‐derived deformation (Zhou, Zhao, et al., 2022). The InSAR‐derived deformations are interpolated to the date of leveling measurements through the linear interpolation of the two InSAR deformation values before and after leveling measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In general, long-term subsidence is higher in warm permafrost areas with high ground ice content, indicating that warm and ice-rich permafrost is more susceptible to extensive ground ice melting. Furthermore, some studies have also detected strong subsidence/uplift signals around certain lakes, suggesting that changes in local hydrological conditions may induce localized permafrost degradation/augmentation [33][34][35].…”
Section: Introductionmentioning
confidence: 99%